Contribution Analysis Interpersonal Communication on Secretarial Services at Pt X - Paramitha Teti, Octaviani (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
In its implementation in the social environment, communication plays an important role in the continuity of interaction. Examining further about interaction, interpersonal communication is one focus that emphasizes the process that occurs between two individuals or groups to share information. This study aims to analyze that interpersonal communication with the application of social penetration theory plays an important role in secretarial services. Therefore, this study aims to understand the contribution of interpersonal communication in secretarial services at PT X. Data were analyzed using pre-research, interviews, literature studies, and documentation, using descriptive qualitative (QD) research methods, using primary and secondary data sources. The results showed that the contribution of interpersonal communication can have a positive impact in the form of the level of communication openness experienced by workers at PT X. This research seeks to provide insight into the contribution of interpersonal communication in dealing with dynamic situations in the realm of the work environment, especially in secretarial services.